Near-infrared quantum dot for light-emitting device and preparation method and application of near-infrared quantum dot
By preparing near-infrared quantum dots of CuInSe2:Zn2+@ZnSe and other types, and combining with the ZnSe shell, the problems of low quantum yield and poor stability in the prior art are solved, and efficient and stable near-infrared quantum dot phosphors are achieved, which are suitable for light conversion applications of near-infrared micro-LED.
Patent Information
- Application Number
- CN202311583782.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-24
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-11-24
AI Technical Summary
The existing Pb/Cd-free near-infrared quantum dot phosphors have problems with low quantum yield and poor photothermal stability, which limits the light conversion efficiency and service life of near-infrared micro-LED.
Near-infrared quantum dots such as CuInSe2:Zn2+@ZnSe are prepared by thermal injection, solvent-thermal method or ion exchange method. Combined with the ZnSe shell, the stability and quantum yield of the quantum dots are significantly improved.
It realizes efficient preparation of near-infrared quantum dots, with fluorescent quantum yield greater than 80%, good photothermal stability, suitable for excitation of a variety of chips, excellent moisture and heat resistance, and long service life.
Smart Images

Figure CN119529843A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of luminescent materials, and relates to near-infrared quantum dots for light-emitting devices, and a preparation method and application thereof, and in particular to a Pb / Cd-free near-infrared emitting quantum dot phosphor, a preparation method thereof, and an LED light source comprising the phosphor. Background Art
[0002] Since Micro-LED was proposed by Chinese scientist Professor Jiang Hongxing in 2000, a wave of related technical research has been set off worldwide. It has broad application prospects in super-resolution display, artificial intelligence, wearable electronic devices and other fields. Micro-LED has become one of the key technological focuses of international competition, and my country has also invested heavily in the research of micro-LED technology. At present, the research on micro-LED is mainly concentrated in the visible light region. Near-infrared light (700-2500nm) has lower energy and higher biological tissue penetration than visible light, so near-infrared micro-LED has significant advantages and great application value in the fields of biosensing (such as blood oxygen saturation, body fat rate, etc.), AR / VR technology (such as eye tracking), remote sensing and optical communications.
[0003] The defects of near-infrared LED chips, such as low energy conversion efficiency, narrow emission half-width and fixed emission position, greatly limit their application and development in LED, especially micro-LED. To address this problem, scientists have proposed the idea of light conversion LED, using the strategy of blue light chip plus near-infrared phosphor to prepare efficient and flexible near-infrared LED. Since commercial blue light chips have been developed relatively maturely, the core factor affecting the final LED device is the quality of near-infrared phosphor. Through nearly a decade of research, scientists have developed a variety of near-infrared phosphors, such as transition metal ion systems (Cr 3+ ,Cr 4+ ,Fe 3+ ,Ni 2+ and Mn 4+ etc.), rare earth ion system (Eu 2+ ,Nd 3+ ,Yb 3+ ,Pr 3+ , and Tm 3+ etc.), ns 2 Configuration ion system (Sn 2+ ,Bi 2+etc.), organic matter and quantum dot systems. Ion-doped near-infrared phosphors have good stability and quantum yield, but most of them are powders and blocks, which greatly limits their application in micro-LEDs; organic molecules have good plasticity, but have problems of low luminous efficiency and poor stability. In contrast, quantum dots have the advantages of nanoscale size, adjustable emission wavelength, wide excitation range, large absorption cross-section and high quantum yield. They are a type of light conversion material that is currently widely studied and generally favored. Therefore, quantum dots are an ideal type of phosphor for near-infrared micro-LEDs.
[0004] The near-infrared quantum dots currently studied are mainly II-VI and IV-VI semiconductors, such as CdSe, CdTe and PbSe. Although they have good optical properties, the heavy metal elements (Cd 2+ and Pb 2+ etc.) are strictly restricted by the United States, the European Union and other countries and regions. At present, near-infrared quantum dot phosphors that do not contain Pb / Cd mainly have the problems of low quantum yield (<70%) and poor photothermal stability, which greatly limits the light conversion efficiency and service life of the device. In 2020, Liu et al. first applied non-toxic quantum dots to near-infrared mini-LEDs (Chem. Commun. 2020, 56, 8285), but due to poor stability, the maximum LED irradiation power was only 10.9mW, and there was no report on the application of non-toxic quantum dots to near-infrared micro-LEDs. In addition, how to avoid coffee rings, the uniform dispersion and stability of phosphors, and the morphology and size control and repeatability of micron-scale arrays are all core issues facing near-infrared quantum dot micro-LEDs. Therefore, it is crucial to develop a class of non-toxic, efficient and stable quantum dot phosphors, and to controllably assemble the phosphors at the micron scale for the development of near-infrared micro-LEDs. Summary of the invention
[0005] In order to improve the deficiencies of the prior art, the present invention provides a near-infrared quantum dot for a light-emitting device, a preparation method thereof, and LED applications, especially near-infrared quantum dots for mini-LED and micro-LED.
[0006] In a first aspect, the present invention provides a near-infrared quantum dot for a light-emitting device, wherein the quantum dot can be selected from CuInSe 2 、CuInTe 2 、AgInSe 2 、AgInTe 2 、CuInSe 2 :Zn 2+ 、CuInTe 2 :Zn 2+ 、AgInSe 2:Zn 2+ 、AgInTe 2 :Zn 2 + 、CuInSe 2 @ZnS、CuInTe 2 @ZnS、AgInSe 2 @ZnS、AgInTe 2 @ZnS、CuInSe 2 :Zn 2+ @ZnS、CuInTe 2 :Zn 2+ @ZnS、AgInSe 2 :Zn 2+ @ZnS、AgInTe 2 :Zn 2+ @ZnS、AgInSe 2 @ZnSe、AgInTe 2 @ZnSe、CuInSe 2 :Zn 2+ @ZnSe、CuInTe 2 :Zn 2+ @ZnSe、AgInSe 2 :Zn 2+ @ZnSe and AgInTe 2 :Zn 2+ @One or more of ZnSe quantum dots, preferably AgInSe 2 @ZnSe、AgInTe 2 @ZnSe、CuInSe 2 :Zn 2+ @ZnSe、CuInTe 2 :Zn 2+ @ZnSe and AgInSe 2 :Zn 2 + @ZnSe one or more, such as CuInSe 2 :Zn 2+ @ZnSe quantum dots.
[0007] According to an embodiment of the present invention, the quantum dots can be excited by light of 250 to 600 nm, emitting near-infrared light with a wavelength of 650 to 1500 nm, with an emission peak in the range of 700 to 1300 nm and a half-width greater than 170 nm. Preferably, the emission wavelength of the quantum dots is 650 to 1000 nm, with an emission peak of 700 to 800 nm.
[0008] According to an embodiment of the present invention, the average particle size of the quantum dots is 1 to 30 nm, and 6 nm is exemplified.
[0009] According to an embodiment of the present invention, the fluorescence quantum yield of the quantum dots is greater than 80%, preferably greater than 85%, and further preferably greater than 92%, for example 92.8%.
[0010] According to an embodiment of the present invention, the quantum dots can maintain a luminescence intensity of more than 80%, preferably more than 85%, after being stored at room temperature for 150 days. For example, the CuInSe 2 :Zn 2+ @ZnSe quantum dots can still maintain 86.9% of the luminescence intensity after 150 days.
[0011] In a second aspect, the present invention provides a method for preparing near-infrared quantum dots as described above, comprising preparing the quantum dots by a hot injection method, a solvothermal method or an ion exchange method, with the hot injection method being an example.
[0012] Preparation of AInB by hot injection 2 :aZn 2+ @ZnSe includes the following steps:
[0013] S1. A salt, In salt, optionally with or without Zn salt, are mixed with a solvent to obtain a first solution, and a second solution containing B powder is added to react to obtain AInB 2 :aZn 2+ , wherein A is selected from Ag or Cu, B is selected from Se or Te, and a is 0 or 1;
[0014] S2. Add Zn salt containing shell structure to AInB 2 :aZn 2+ The third solution is mixed to obtain a third solution, and a fourth solution containing Se powder is added to the third solution and mixed to react to obtain AInB 2 :aZn 2+ @ZnSe.
[0015] According to an embodiment of the present invention, in step S1, the A salt, In salt and Zn salt are all soluble salts, and the B powder is Se powder or Te powder.
[0016] According to an embodiment of the present invention, in step S1, the molar ratio of Cu / In is greater than 0.0 and less than or equal to 1.2, and the molar ratio of Zn / In is greater than 0.0 and less than or equal to 1.0, for example, Cu / In=0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, and Zn / In=0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0.
[0017] According to an embodiment of the present invention, the solvent is selected from a mixed solvent of oleic acid, oleylamine, dodecanethiol and octadecene.
[0018] According to an embodiment of the present invention, the mixing in step S1 is performed under anhydrous and oxygen-free conditions, and the mixing temperature is 100-140°C, preferably 110-130°C, for example 120°C.
[0019] According to an embodiment of the present invention, in step S1, when B is Se, the preparation method of the second solution is as follows: Se powder is added to a mixed solution of oleylamine and dodecanethiol and dissolved. Preferably, the volume ratio of oleylamine and dodecanethiol is (2-3):1, preferably the volume ratio of oleylamine and dodecanethiol is (2.1-2.6):1, for example, 2:1, 2.2:1, 2.3:1, 7:3, 2.5:1, 2.7:1.
[0020] According to an embodiment of the present invention, adding Se powder into a mixture of oleylamine and dodecanethiol and dissolving the mixture comprises the following steps: adding Se powder into a mixture of oleylamine and dodecanethiol and dissolving the mixture by ultrasonication at room temperature.
[0021] According to an embodiment of the present invention, in step S1, when B is Te, the second solution is dissolved using a conventional dissolution method in the art.
[0022] According to an embodiment of the present invention, the reaction in step S1 comprises the following steps: heating the first solution to a reaction temperature of 180 to 230° C., injecting the second solution and reacting at the reaction temperature for 2 to 30 minutes.
[0023] According to an embodiment of the present invention, the reaction temperature in step S1 is 200-220°C, and the reaction time is 15-25 min. For example, the reaction temperature is 180°C, 190°C, 210°C, 220°C, and the reaction time is 10 min, 15 min, 20 min, 25 min.
[0024] According to an embodiment of the present invention, the preparation of the third solution in step S2 comprises the following steps: adding zinc stearate to the AInB obtained in step S1; 2 :aZn 2+A mixed solvent is added to the solution to remove water and oxygen from the reaction system.
[0025] According to an embodiment of the present invention, the mixed solvent includes oleic acid, oleylamine and octadecene.
[0026] According to an embodiment of the present invention, the mixing of the mixed solvent is performed at a temperature of 100-150°C, preferably 110-120°C, for example 120°C.
[0027] According to an embodiment of the present invention, the preparation method of the fourth solution in step S2 is the same as the preparation method of the second solution when B is Se.
[0028] According to an embodiment of the present invention, in step S2, the fourth solution is added to the third solution for mixing, and the reaction comprises the following steps: firstly heating the third solution to 170-210° C., adding the fourth solution and reacting for 70-90 minutes.
[0029] According to an embodiment of the present invention, step S2 further includes the following steps: washing the reaction product and centrifuging to obtain quantum dots.
[0030] In a third aspect, the present invention provides a phosphor for a light-emitting device, wherein the phosphor comprises the near-infrared quantum dots as described above.
[0031] In a fourth aspect, the present invention provides an application of the above-mentioned near-infrared quantum dots or phosphors in photoluminescence, preferably for LEDs, such as mini-LEDs or micro-LEDs.
[0032] In a fifth aspect, the present invention provides a mini-LED, on which the near-infrared quantum dots or phosphors as described above are arranged.
[0033] According to an embodiment of the present invention, the mini-LED includes an LED chip, and near-infrared quantum dots or phosphors are arranged on the LED chip.
[0034] According to an embodiment of the present invention, the preparation method of setting near-infrared quantum dots or phosphors on an LED chip is as follows: the quantum dots or phosphors are mixed with a glue solution, and coated on the LED chip to form a quantum dot or phosphor layer, wherein the layered structure is a continuous or discontinuous structure.
[0035] According to an embodiment of the present invention, the near-infrared quantum dots or phosphors can be uniformly dispersed in the glue. For example, after the quantum dots are mixed with the glue, they have a substantially Figure 7 Transmission electron micrograph shown.
[0036] According to an embodiment of the present invention, the mass ratio of the near-infrared quantum dots or phosphors to the encapsulation adhesive is 5 to 40 mg / g, and 25 mg / g is exemplified.
[0037] Preferably, the LED chip may be a purple light, blue light or red light chip, with a blue light chip being an example.
[0038] According to an embodiment of the present invention, the adhesive liquid may be a heat-curing adhesive or a UV-curing adhesive, with UV-curing adhesive being an example.
[0039] According to an embodiment of the present invention, an isolation layer is provided between the near-infrared quantum dots or phosphor layer and the LED chip.
[0040] According to an embodiment of the present invention, a protective layer is disposed on the near-infrared quantum dots or phosphor layer.
[0041] According to an embodiment of the present invention, the mini-LED has substantially the following Figure 7 The irradiance flux diagram shown is under double 85 aging (referring to the conditions of temperature of 85°C and humidity of 85%).
[0042] In a sixth aspect, the present invention further provides a micro-LED, wherein the micro-LED light-emitting device comprises an LED chip, and the LED chip is distributed with the near-infrared quantum dots or phosphors as described above.
[0043] According to an embodiment of the present invention, the method for preparing the micro-LED comprises the following steps:
[0044] a) dispersing near infrared quantum dots or phosphors in a printing solvent to form ink;
[0045] b) Use ink to print on LED chips to form micro-LEDs.
[0046] According to an embodiment of the present invention, the printing solvent is one or more solvents selected from octane, decane, dodecane, dodecanethiol, ethylene glycol, o-dichlorobenzene, cyclohexylbenzene and polytetrafluoroethylene, and polytetrafluoroethylene is exemplified.
[0047] According to an embodiment of the present invention, the mass ratio of quantum dots or phosphors to solvent in the ink is 10-60 mg / g, and 20 mg / g is exemplified.
[0048] According to an embodiment of the present invention, the quantum dots can be uniformly dispersed in a printing solvent. For example, the ink has substantially Fig.12 Transmission electron micrograph shown.
[0049] According to an embodiment of the present invention, the quantum dots may be printed on the chip by inkjet printing, electrofluidic printing or transfer printing technology, with electrofluidic printing being an example.
[0050] According to an embodiment of the present invention, the LED chip may be a purple light, blue light or red light chip, with a blue light chip being exemplified.
[0051] According to an embodiment of the present invention, before step b), the following step is also included: first spin coating a contact layer on the surface of the light-transmitting layer of the LED chip, the contact angle between the contact layer and the ink is 10 to 30°, preferably the contact angle between the contact layer and the ink is 10 to 20°, for example, 19.75°.
[0052] According to an embodiment of the present invention, the hydrophobic layer material is selected from at least one of PEDOT (3,4-ethylenedioxythiophene monomer), PMMA (polymethyl methacrylate) or PPy (polypyrrole), for example, PEDOT.
[0053] As an example, step b) includes the following steps: spray printing the quantum dot ink on the contact layer, and finally spin coating a layer of ultraviolet light curing glue on the quantum dot layer for protection and packaging.
[0054] According to an embodiment of the present invention, the outer diameter of the needle used in the electrofluidic printing can be 50 μm, 20 μm, 10 μm, 5 μm, 2 μm and 1 μm, with 2 μm being an example.
[0055] According to an embodiment of the present invention, the quantum dots form a dot matrix structure or a linear structure on the LED chip.
[0056] According to an embodiment of the present invention, each dot in the dot matrix structure is a luminous pixel, and the diameter of the luminous pixel is less than 30 μm, preferably the diameter of the luminous pixel is less than 20 μm, and further preferably, the diameter of the luminous pixel is less than 5 μm.
[0057] According to an embodiment of the present invention, the line width of the linear structure is less than 30 μm, preferably the line width of the linear structure is less than 20 μm, and further preferably, the line width of the linear structure is less than 5 μm.
[0058] According to an embodiment of the present invention, the micro-LED has substantially Fig.17 Or the fluorescent image described in 18.
[0059] The beneficial effects of the present invention are:
[0060] The present invention has the following advantages: 1) The near-infrared quantum dot phosphor has good photothermal stability, the yield of near-infrared quantum dots is greater than 80%, and can reach up to 92.8% at the highest, with high light absorption efficiency, can well prevent blue light leakage, can be excited by a variety of ultraviolet-blue light-red light chips, has a wide range of applicable scenarios, excellent moisture and heat resistance, and long service life; 2) The near-infrared quantum dots in the present invention do not contain Pb / Cd heavy metal toxic elements, which conforms to the concept of green chemistry; 3) The quantum dots can maintain excellent dispersibility in the encapsulation glue and inkjet ink to prevent luminescence quenching caused by aggregation; 4) A quantum dot luminescent array with a size of less than 30 μm can be prepared, with high luminous intensity, regular shape, and no coffee ring, compared with The chip cutting and mass transfer process is simpler, low-cost, and highly repeatable, and can be mass-produced; 5) The inventor unexpectedly discovered that when preparing the core structure of near-infrared quantum dots, only when the oleylamine and dodecanethiol dissolved in Se powder are in a specific ratio (2-3):1, can near-infrared quantum dots with a quantum yield greater than 90% be obtained. Under other ratios, the obtained quantum yield drops sharply; 6) When quantum dots are used for micro-LEDs in the present invention, they are first configured into ink and then printed onto the surface of the LED chip. The contact angle between the contact layer on the surface of the LED chip and the ink is 10-30°, so that the ink has no tailing during printing and forms a uniform structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 The CuInSe prepared in Example 1 of the present invention 2 :Zn 2+ @Excitation and emission spectra of ZnSe quantum dots.
[0062] Figure 2 The CuInSe prepared in Example 1 of the present invention 2 :Zn 2+ @Transmission electron microscopy image of ZnSe quantum dots dispersed in n-hexane.
[0063] Figure 3 The CuInSe prepared in Example 1 of the present invention 2 :Zn 2+ Quantum dots and CuInSe 2 :Zn 2+ @The luminescence intensity of ZnSe quantum dots changes over time.
[0064] Figure 4 It is a comparison chart of emission spectra and quantum yields of Example 1, Example 2 and Example 3.
[0065] Figure 5 CuInSe synthesized in Example 1 and Comparative Example 1 of the present invention 2 :Zn 2+@ZnSe quantum dot emission spectrum.
[0066] Figure 6 The CuInSe synthesized in Example 1 and Comparative Example 2 of the present invention 2 :Zn 2+ 、CuInSe 2 :Zn 2+ @ZnSe and CuInSe 2 :Zn 2+ @ZnS quantum dot emission and quantum yield comparison chart.
[0067] Figure 7 CuInSe in Example 4 of the present invention 2 :Zn 2+ @Transmission electron microscopy image of ZnSe quantum dots in UV-curing adhesive.
[0068] Figure 8 This is a schematic diagram of the structure of the near-infrared mini-LED prepared in Example 4 of the present invention.
[0069] Fig. 9 This is a graph showing the variation of the irradiance flux of the near-infrared mini-LED double 85 aging over time prepared in Example 4 of the present invention.
[0070] Fig.10 This is a transmission electron microscopy image of the quantum dots prepared in Comparative Example 3 of the present invention in the mini-LED coating liquid.
[0071] Fig.11 This is a comparison chart of the working spectra and irradiation flux of the mini-LED prepared in Example 4 of the present invention and Comparative Example 3.
[0072] Fig.12 This is a transmission electron microscope image of quantum dots in micro-LED printing ink according to Example 5 of the present invention.
[0073] Fig.13 Schematic diagram of the structure of the near-infrared micro-LED in Example 5 of the present invention.
[0074] Fig.14 This is a high-magnification physical image of the dot matrix printed by comparative example 4 of the present invention.
[0075] Fig.15 This is a dot matrix scanning electron microscope image printed by comparative example 5 of the present invention.
[0076] Fig.16 This is a scanning electron microscope image of the micro array printed in Example 5 of the present invention.
[0077] Fig.17 This is the micro array fluorescent image printed in Example 5 of the present invention.
[0078] Fig.18 These are the bright field image and fluorescent image of the micro five-pointed star and wavy line printed in Example 5 of the present invention. DETAILED DESCRIPTION
[0079] The following will further describe the quantum dots of the present invention and its preparation method and application in combination with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope of protection of the present invention.
[0080] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0081] Example 1
[0082] CuInSe 2 :Zn 2+ The preparation method of @ZnSe quantum dot phosphor is as follows:
[0083] 1) Add 0.1mmol cuprous iodide, 0.2mmol indium acetate and 0.2mmol zinc acetate into a three-necked flask (Cu / In=0.5, Zn / In=1.0), then add 0.8mL oleic acid, 0.8mL oleylamine, 1mL dodecanethiol and 10mL octadecene to dissolve (oleic acid, oleylamine, dodecanethiol and octadecene in a ratio of 0.8:0.8:1:10), heat to 120°C with nitrogen under stirring, evacuate / nitrogen cycle 5 times to remove water and oxygen in the system, and obtain a light yellow first solution. Dissolve 0.4mmol selenium powder in a mixture of 0.7mL oleylamine and 0.3mL dodecanethiol (oleylamine and dodecanethiol 7:3), and fully dissolve under ultrasonication for 20min at room temperature to obtain a brown-red second solution.
[0084] 2) The first solution was heated to 220°C, and the second solution was rapidly injected thereinto. After the reaction was kept at 220°C for 20 minutes, the solution was cooled to room temperature in an ice water bath to obtain an intermediate product solution. The intermediate product was CuInSe 2 :Zn 2+ Quantum dots.
[0085] 3) Add 0.3 mmol zinc stearate to the intermediate product solution obtained in 2), then add 0.4 mL oleic acid, 0.2 mL oleylamine, 10 mL octadecene, heat to 120°C with stirring and nitrogen, and cycle 5 times of vacuum / nitrogen to remove water and oxygen in the system to obtain a third solution. Dissolve 0.4 mmol selenium powder in a mixture of 0.5 mL oleylamine and 0.5 mL dodecanethiol, and fully dissolve under ultrasonication for 20 min at room temperature to obtain a fourth solution.
[0086] 4) After the third solution is heated to 200°C, the fourth solution is added dropwise within 1 hour, and the reaction is kept at 200°C for another 30 minutes, and then cooled to room temperature in an ice water bath to obtain a reaction product solution. The reaction product is CuInSe 2 :Zn 2+ @ZnSe.
[0087] 5) The reaction product of 4) was washed with a mixture of ethanol and n-hexane (volume ratio of ethanol to n-hexane was 1:1) and centrifuged to obtain CuInSe 2 :Zn 2+ @ZnSe quantum dot phosphor, dispersed in n-hexane.
[0088] Figure 1 CuInSe 2 :Zn 2+ @The excitation and emission spectra of ZnSe quantum dots show that the quantum dots exhibit broadband excitable characteristics from 250-600nm, and the emission spectrum is from 600 to 1000nm.
[0089] Figure 2 CuInSe 2 :Zn 2+ @Transmission electron microscope image of ZnSe quantum dots dispersed in n-hexane. It can be seen that the quantum dots are tetrahedral in shape, uniform in size, with an average particle size of about 6nm, and have good monodispersity.
[0090] Figure 3 CuInSe 2 :Zn 2+ @ZnSe quantum dots before and after encapsulation, the luminescence intensity changes over time. It can be seen that CuInSe before encapsulation 2 :Zn 2+ The luminescence of quantum dots was completely quenched after being stored at room temperature for 40 days, while CuInSe 2 :Zn 2+ @ZnSe quantum dots can still maintain 86.9% of the luminescence intensity after 150 days, indicating that the ZnSe shell can significantly improve the stability of quantum dot phosphors.
[0091] Example 2
[0092] The difference between this embodiment and embodiment 1 is that the feeding amount of step 1) is changed to: 0.08mmol cuprous iodide, 0.2mmol indium acetate and 0.16mmol zinc acetate are added to a three-necked flask (Cu / In=0.4, Zn / In=0.8), and then 0.6mL oleic acid, 0.6mL oleylamine, 0.8mL dodecanethiol and 10mL octadecene are added to dissolve (the ratio of oleic acid, oleylamine, dodecanethiol and octadecene is 0.6:0.6:0.8:10); the reaction conditions of step 2) are changed to: keep warm at 200°C for 25min, and the other steps are the same as in embodiment 1.
[0093] Example 3
[0094] The difference between this embodiment and embodiment 1 is that the feeding amount of step 1) is changed to: 1.2mmol cuprous iodide, 0.2mmol indium acetate and 0.1mmol zinc acetate are added to a three-necked flask (Cu / In=0.6, Zn / In=0.5), and then 1mL oleic acid, 1mL oleylamine, 1mL dodecanethiol and 10mL octadecene are added to dissolve (the ratio of oleic acid, oleylamine, dodecanethiol and octadecene is 1:1:1:10). The reaction conditions of step 2) are changed to: keep warm for 15min at 230°C, and the other steps are the same as those of embodiment 1.
[0095] Figure 4 The emission spectra and quantum yield comparison of the quantum dots of Example 1, Example 2 and Example 3 show that the CuInSe synthesized with different feed ratios 2 :Zn 2+ @ZnS quantum dot emission peak position slightly shifted, Example 1 peak position at 741nm, Example 2 peak position at 718nm, Example 3 peak position at 770nm, all located in the near infrared region, and the quantum yield can reach more than 80% (Example 1 is 92.8%, Example 2 is 84.1%, Example 3 is 80.7%). This shows that the quantum dots prepared by the present invention have a higher quantum yield.
[0096] Comparative Example 1
[0097] The difference between this comparative example and Example 1 is that the selenium powder in step 1) and step 3) is dissolved in 0.5 mL of oleylamine and 0.5 mL of dodecanethiol (oleylamine and dodecanethiol 1:1), and the other steps are the same as Example 1.
[0098] like Figure 5 As shown in the figure, the comparative test found that the luminescence intensity of the quantum dot phosphor prepared in Comparative Example 1 was only half of that in Example 1, indicating that the ratio of oleylamine and dodecanethiol for dissolving selenium powder had a significant effect on CuInSe 2 :Zn 2+ @ZnSe quantum dots have a great impact on the luminescence efficiency.
[0099] Comparative Example 2
[0100] Preparation of CuInSe 2 :Zn 2+ @ZnS quantum dot phosphor: This comparative example is different from Example 1 in that the selenium powder in step 3) is replaced with sulfur powder.
[0101] Figure 6 CuInSe 2 :Zn 2+ Quantum Dots and CuInSe 2 :Zn 2+ @ZnSe and CuInSe 2 :Zn 2+ @ZnS quantum dot emission and quantum yield comparison chart. Compared with CuInSe 2 :Zn 2+ Quantum dots, CuInSe 2 :Zn 2+ @ZnSe and CuInSe 2 :Zn 2+ @ZnS quantum dots emission peak position does not change much, CuInSe 2 :Zn 2+ The quantum yield of ZnSe-containing CuInSe is 28.6% 2 :Zn 2 + @ZnSe quantum yield increased to 92.8%, while CuInSe containing ZnS 2 :Zn 2+ @ZnS quantum yield only increased to 46.9%, indicating that the ZnSe shell layer has a better effect on improving the luminous efficiency.
[0102] Example 4
[0103] Based on CuInSe 2 :Zn 2+ The preparation method of near-infrared mini-LED of @ZnSe quantum dot phosphor is as follows:
[0104] 1) Take 25 mg of CuInSe prepared in Example 1 2 :Zn 2+ @ZnSe quantum dots were dispersed in 5 mL of chloroform, and 1 g of UV-curable glue was added. The mixture was evenly mixed by ultrasonic treatment for 10 min. The chloroform was evaporated by rotary evaporator to obtain the mini-LED quantum dot coating liquid.
[0105] 2) First, evenly apply 15 mg of UV-curable glue on the 2835 LED chip and cure it under UV light for 10 minutes to form an isolation layer; then evenly apply 60 mg of quantum dot coating liquid on the isolation and cure it under UV light for 10 minutes to form a quantum dot layer; finally, evenly apply 15 mg of UV-curable glue on the quantum dot layer and cure it under UV light for 10 minutes to form a protective layer, and encapsulate it into a mini-LED device.
[0106] Figure 7 CuInSe 2 :Zn 2+ @Transmission electron microscope image of ZnSe quantum dots in UV-curing adhesive. It can be seen that the nanoparticles are well dispersed.
[0107] Figure 8 A schematic diagram of the structure of near-infrared mini-LED is given.
[0108] Fig. 9 A radiant flux diagram of the near-infrared mini-LED prepared in this embodiment under double 85 aging is given. It can be seen from the figure that under the condition that the aging time of the mini-LED prepared in this embodiment is greater than 70h, the radiant flux can still reach 94.5%.
[0109] Comparative Example 3
[0110] The difference between this comparative example and Example 2 is that the chloroform in step 1) is replaced with n-hexane, and the other steps are the same as Example 2 to prepare a mini-LED device.
[0111] Fig.10 The transmission electron microscope image of the quantum dot-UV glue mixture prepared in this comparative example shows that the quantum dots are in an agglomerated state. Fig.11 As shown, the irradiation flux of the mini-LED prepared in Comparative Example 3 is 10.3mW@350mA, and the irradiation flux of the mini-LED prepared in Example 4 is 88.7mW@350mA, indicating that the uniform dispersion of quantum dot phosphors is very important for the output efficiency of LED devices. 2 :Zn 2+ @The optimal irradiation flux of the near-infrared mini-LED with ZnSe quantum dot phosphor (88.7mW@350mA) also exceeds the highest irradiation flux of the non-toxic quantum dot near-infrared mini-LED reported in the literature.
[0112] Example 5
[0113] Based on CuInSe 2 :Zn 2+The preparation method of near-infrared micro-LED with @ZnSe quantum dot phosphor is as follows:
[0114] 1) Take 20 mg of CuInSe prepared in Example 1 2 :Zn 2+ @ZnSe quantum dots were dispersed in 5 mL of cyclohexane, and then 1 g of a mixture of polytetrafluoroethylene and thinner (polytetrafluoroethylene mass fraction was 48%) was added, and the mixture was mixed by ultrasonic for 10 min, and the cyclohexane was evaporated by a rotary evaporator to obtain a quantum dot inkjet ink. The viscosity of the inkjet ink was 230 cP.
[0115] 2) Spin-coat a layer of PEDOT (3000 r / min, 1 min) on the surface of the light-transmitting layer of the LED chip, and dry at 150° C. for 15 min to obtain a printing substrate. The contact angle between the printing ink and the substrate is 19.74°.
[0116] 3) Then, the quantum dot inkjet printing ink is loaded into the printing needle tube, the needle aperture is 2 μm, the distance between the needle tip and the substrate is 18 μm, the printing rate is 1 mm / s, the ink-on delay is 30 ms, the ink-dropping is 120 ms, the ink-off delay is 50 ms, the bias is 430 V, the frequency is 100 Hz, and the duty cycle is 20%. The quantum dot ink is printed onto the PEDOT surface to form a micron-scale micro light conversion array with regular shape and uniform dispersion.
[0117] 4) The product of step 3) is dried at 75° C. for 30 min, and then a layer of encapsulation glue is spin-coated on the outermost layer to encapsulate into a micro-LED device.
[0118] Fig.12 CuInSe 2 :Zn 2+ @ZnSe quantum dots in the transmission electron microscope image of the inkjet printing ink, it can be seen that CuInSe 2 :Zn 2+ @ZnSe quantum dots have good dispersion and no agglomeration.
[0119] Fig.13 A schematic diagram of the structure of near-infrared micro-LED is given.
[0120] Comparative Example 4
[0121] The difference between this comparative example and Example 5 is that the mixed solution of polytetrafluoroethylene and thinner in step 1) is replaced with a mixed solution of n-octane and dodecane (3:7 of n-octane and dodecane).
[0122] Fig.14This is a high-magnification physical image of the dot matrix printed by comparative example 4. It can be seen that the printed dots gradually become smaller, have obvious coffee rings, and also appear to be aggregated into clusters / needles, indicating that the physical and chemical properties of the printing ink are crucial to the shape and repeatability of the final micro array.
[0123] Comparative Example 5
[0124] The difference between this comparative example and Example 5 is that the PEDOT in step 2) is replaced by PDMS.
[0125] Fig.15 This is a scanning electron microscope image of the dot array printed in comparative example 5. It can be seen that the printed dots have serious tailing phenomenon, and some dots are even completely interconnected, indicating that the affinity between the substrate and the printing ink is also very important to the shape of the final micro array.
[0126] Fig.16 The scanning electron microscope image of the micro array printed in Example 5 is given. It can be seen that the printed dots have regular and complete shapes, uniform sizes, and good repeatability; the printed straight lines also have good morphology and stability. Fig.17 It can be seen that the micro array printed in Example 3 has a strong and uniform fluorescence signal. In addition, Fig.18 The printing effect of Example 5 on complex shapes is also demonstrated. It can be seen that even if a five-pointed star or a wavy line is printed, it can still maintain a uniform and complete structure and have a good fluorescence signal. This shows that the entire array printed by this method has good controllability and stability. It is worth mentioning that the dot matrix diameter printed in Example 5 is less than 5μm, which exceeds the current commercial inkjet printing technology (10-30μm). This is also the first time that non-toxic quantum dots have been used in near-infrared micro-LED arrays below 5 microns.
[0127] The above examples are used to illustrate the specific implementation of the present invention. However, the protection scope of the present invention is not limited to the above exemplary implementation. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A near-infrared quantum dot for a light-emitting device, characterized in that: The quantum dots are selected from CuInSe2, CuInTe2, AgInSe2, AgInTe2, CuInSe2:Zn 2+ 、CuInTe2:Zn 2+ 、AgInSe2:Zn 2+ 、AgInTe2:Zn 2+ , CuInSe2@ZnS, CuInTe2@ZnS, AgInSe2@ZnS, AgInTe2@ZnS, CuInSe2:Zn 2+ @ZnS、CuInTe2:Zn 2+ @ZnS、AgInSe2:Zn 2 + @ZnS、AgInTe2:Zn 2+ @ZnS, AgInSe2@ZnSe, AgInTe2@ZnSe, CuInSe2:Zn 2+ @ZnSe、CuInTe2:Zn 2+ @ZnSe、AgInSe2:Zn 2+ @ZnSe and AgInTe2:Zn 2+ @ZnSe quantum dots, preferably AgInSe2@ZnSe, AgInTe2@ZnSe, CuInSe2:Zn 2+ @ZnSe、CuInTe2:Zn 2+ @ZnSe and AgInSe2:Zn 2+ @ZnSe one or more.
2. The near-infrared quantum dots for light-emitting devices according to claim 1, characterized in that: The quantum dots can be excited by light of 250 to 600 nm, and emit near-infrared light of a wavelength of 650 to 1500 nm, with an emission peak in the range of 700 to 1300 nm. Preferably, the fluorescence quantum yield of the quantum dots is greater than 80%. Preferably, the quantum dots can maintain more than 80% of the luminescence intensity after being stored at room temperature for 150 days.
3. A method for preparing near-infrared quantum dots according to claim 1 or 2, characterized in that: The quantum dots are prepared by a hot injection method, a solvent thermal method or an ion exchange method, with the hot injection method being an example. Preferably, AInB2:aZn is prepared by hot injection. 2+ @ZnSe includes the following steps: S1. A salt, In salt, optionally with or without Zn salt, are mixed with a solvent to obtain a first solution, and a second solution containing B powder is added to react to obtain AInB2:aZn 2+ , wherein A is selected from Ag or Cu, B is selected from Se or Te, and a is 0 or 1; S2. Add Zn salt to AInB2:aZn 2+ The third solution is mixed to obtain a third solution, and the fourth solution containing Se powder is added to the third solution and mixed, and reacted to obtain AInB2:aZn 2+ @ZnSe.
4. The preparation method according to claim 3, characterized in that: In step S1, the molar ratio of Cu / In is greater than 0.0 and less than or equal to 1.2, and the molar ratio of Zn / In is greater than 0.0 and less than or equal to 1.0; Preferably, in step S1, when B is Se, the second solution is prepared by adding Se powder into a mixture of oleylamine and dodecanethiol and dissolving the mixture, wherein the volume ratio of oleylamine to dodecanethiol is (2-3):
1. Preferably, the reaction in step S1 comprises the following steps: heating the first solution to a reaction temperature of 180 to 230° C., injecting the second solution and reacting at the reaction temperature for 2 to 30 minutes.
5. The preparation method according to claim 3 or 4, characterized in that: The preparation of the third solution in step S2 comprises the following steps: adding zinc stearate to the AInB2:aZn obtained in step S1; 2+ The mixed solvent is added to the solution and mixed to remove water and oxygen in the reaction system. The mixed solvent is added and mixed at a temperature of 100 to 150°C. Preferably, in step S2, the fourth solution is added to the third solution for mixing, and the reaction comprises the following steps: firstly, the third solution is heated to 170-210° C., and the fourth solution is added for reaction for 70-90 minutes.
6. A phosphor for a light-emitting device, the phosphor comprising the near-infrared quantum dots according to claim 1 or 2 or the near-infrared quantum dots prepared by the method according to any one of claims 3 to 5.
7. A mini-LED, characterized in that: The mini-LED is provided with the near-infrared quantum dots described in any one of claims 1-2, the near-infrared quantum dots prepared by the method described in any one of claims 3-5, or the phosphor described in claim 6. Preferably, the mini-LED comprises an LED chip, and near-infrared quantum dots or phosphors are arranged on the LED chip.
8. The mini-LED according to claim 7, characterized in that: The preparation method of setting near-infrared quantum dots or phosphors on an LED chip is as follows: mixing the quantum dots or phosphors with glue and coating them on the LED chip. Preferably, the mass ratio of the near-infrared quantum dots or phosphors to the encapsulation adhesive is 5-40 mg / g.
9. A micro-LED, characterized in that: The micro-LED light-emitting device comprises an LED chip, on which the near-infrared quantum dots described in any one of claims 1 to 2 or the near-infrared quantum dots prepared by the method described in any one of claims 3 to 5 or the phosphor described in claim 6 are distributed. Preferably, the method for preparing the micro-LED comprises the following steps: a) dispersing near infrared quantum dots or phosphors in a printing solvent to form ink; b) Use ink to print on LED chips to form micro-LEDs. Preferably, the printing solvent is selected from one or more solvents of octane, decane, dodecane, dodecanethiol, ethylene glycol, o-dichlorobenzene, cyclohexylbenzene and polytetrafluoroethylene. Preferably, the mass ratio of quantum dots or phosphors to solvent in the ink is 10-60 mg / g.
10. The micro-LED according to claim 9, characterized in that: Before the step b), the method further includes the following steps: spin coating a contact layer on the surface of the light-transmitting layer of the LED chip, wherein the contact angle between the contact layer and the ink is 10 to 30 degrees. Preferably, the quantum dots form a dot matrix structure or a linear structure on the LED chip. Preferably, each dot in the dot matrix structure is a luminous pixel, and the diameter of the luminous pixel is less than 30 μm. Preferably, the line width of the linear structure is less than 30 μm.
Citation Information
Patent Citations
Synthesis method of Zn-CuInSe2 / ZnSe core-shell quantum dots
CN111518540A